2022
DOI: 10.3390/cancers15010201
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency of Cancer-Predisposition Gene Mutations in Liver Transplant Candidates with Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) mainly stems from liver cirrhosis and its genetic predisposition is believed to be rare. However, two recent studies describe pathogenic/likely pathogenic germline variants (PV) in cancer-predisposition genes (CPG). As the risk of de novo tumors might be increased in PV carriers, especially in immunosuppressed patients after a liver transplantation, we analyzed the prevalence of germline CPG variants in HCC patients considered for liver transplantation. Using the panel NGS target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A study in the Czech Republic consisted of 334 patients with HCC and 1662 controls from the general population who had their DNA sequenced with an in-house panel 226 cancer-related genes. 104 Within the patient cohort, a total of 47 patients carried P/LP variants representing a prevalence of 14.1%. However, a noteworthy finding was that only 7 of the 334 patients (2.1%) harbored a P/LP variant in established cancer-associated genes, specifically PMS2 , NBN , FH , or RET .…”
Section: Rare Variants In Cancer-associated Genes In Hepatocellular C...mentioning
confidence: 99%
“…A study in the Czech Republic consisted of 334 patients with HCC and 1662 controls from the general population who had their DNA sequenced with an in-house panel 226 cancer-related genes. 104 Within the patient cohort, a total of 47 patients carried P/LP variants representing a prevalence of 14.1%. However, a noteworthy finding was that only 7 of the 334 patients (2.1%) harbored a P/LP variant in established cancer-associated genes, specifically PMS2 , NBN , FH , or RET .…”
Section: Rare Variants In Cancer-associated Genes In Hepatocellular C...mentioning
confidence: 99%
“…The NGS libraries were prepared with KAPA HyperPlus/EvoPlus Library Preparation Kits (Roche) according to the manufacturer with minor modifications described previously. 19,21,36 The target regions were captured with pooled CZECANCA and PRSMAN panels in a 2:1 ratio. Sequencing was performed with NextSeq 500 instruments (Illumina, San Diego, California).…”
Section: Next-generation Sequencing Panel Analysismentioning
confidence: 99%
“…A recent meta-analysis of studies in prostate cancer patients confirmed an association between the NBN germline alterations and increased prostate cancer risk (with OR = 6.4 and OR = 7.5 for the total and Caucasian populations, respectively) [ 93 ]. Episodic reports have associated germline NBN variants with the risk of cervical [ 94 ] and hepatocellular carcinoma [ 95 ], medulloblastoma [ 96 ], or hematopoietic malignancies [ 94 , 97 ]. Interestingly, recent analysis of 34,046 US patients by Belhadj et al confirmed the lack of association with BC, but suggests a potential role of NBN germline pathogenic variants in the development of other cancer types [ 98 ].…”
Section: Heterozygous Germline Alterations Of Mrn Complex Genes In Ca...mentioning
confidence: 99%
“…Even more than for NBN , the clinical significance of heterozygous germline alterations in the MRE11 and RAD50 genes remains elusive. Analyses of the RAD50 gene have shown that its germline variants are associated with colorectal [ 99 ], pancreatic [ 100 ], hepatocellular [ 95 ] or breast cancer risk [ 101 , 102 , 103 ]. The recurrent, loss-of-function, germline, Finnish founder variant c.687delT (p.Leu229Ter) has been associated with increased breast cancer risk (OR = 4.3; 95% CI 1.5–12.5) in the Finnish population [ 101 ].…”
Section: Heterozygous Germline Alterations Of Mrn Complex Genes In Ca...mentioning
confidence: 99%